Synthetic and natural polymers in modern polymeric materials. Part I. Polymers from renewable resources and polymer nanocomposites - Florjańczyk, Z.; Dębowski, M.; Chwojnowska, E.; Łokaj, K.; Ostrowska, J. (Polimery, 2022)
The currents trends in polymer industry are presented on the basis of monographs and other sources and reports on the state and prospects of polymeric materials development. Fundamental achievements in research on the manufacturing of polymers from natural resources as well as on preparation of nanofillers suitable for polymer composites are described. Special attention has been paid to the problems related to use of biotechnology in the syntheses of monomers and various types of polymers, as well as to nanocomposites with layered aluminosilicates (which fields of practical applications widen) or another fillers (e.g. 1-3, Table 1).